Foundations of recognition theory to solve the problem of diversity in the contemporary state - Al-Khalil, Raad Abdul-Jalil Mustafa; Mawlood, Imad Ahmad (Journal of Legal and Political Studies, 2019)
The theory of recognition is one of the theories of pluralism that has emerged to address the problematic of ethnic and cultural diversity in contemporary state by recognizing diversity and pluralism in response to monotheistic theories that seek to abolish or marginalize cultural diversity by adopting melting-pot policy. The theory of recognition of multiple forms and form , each of which emphasizes a certain aspect of recognition , is reflected . including ensuring the preservation of the cultural identity of the people , justice through redistribution of economic resources , gain the appreciation of self – esteem through recognition by the other , emphasis on tolerance and dialogue , sharing power between groups … etc, we highlight fears of recognition by centrists and unionists on the grounds that recognition paves the way for destabilization and the dismantling of the state .
Keywords: Recognition; Diversity; Pluralism; Ethnic; Cultur; justice; Redistribution; Tolerance; Dialogue